A BALANCE IN CHARACTER AND KNOWLEDGE ACHIEVED THROUGH LEARNED VALUES AND TALENT-BASED CONCEPTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 3 December 2016 A balance between character and knowledge can be achieved as students learn, unlearn, relearn and colearn, and move to the next level through learned values and which are talentbased, which graduates can then adapt to become problemsolvers in the future.